Analysis of Plasmacytoid and Myeloid Dendritic Cells in Nasal Epithelium - Hartmann, Evelyn (American Society for Microbiology, 2006)
The role of plasmacytoid dendritic cells (PDC), the major producers of alpha interferon upon viral infection, in the nasal mucosa is largely unknown. Here we examined the presence of PDC together with myeloid dendritic cells (MDC) in the nasal epithelia of healthy individuals, of asymptomatic patients with chronic nasal allergy, of patients undergoing steroid therapy, and of patients with infectious rhinitis or rhinosinusitis. Considerable numbers of PDC and MDC could be detected in the nasal epithelium. Furthermore, we demonstrate the expression of SDF-1, the major chemoattractant for PDC, in the nasal epithelium. PDC levels were significantly lower for patients with allergies than for healthy individuals. Interestingly, PDC and MDC were almost absent from patients who received treatment with glucocorticoids, while very high numbers of PDC were found for patients with recent upper respiratory tract infections. Our results demonstrate for the first time a quantitative analysis of PDC and MDC in the healthy nasal epithelium and in nasal epithelia from patients with different pathological conditions. With the identification of PDC, the major target cell for CpG DNA or immunostimulatory RNA, in the nasal epithelium, this study forms the basis for a local nasal application of such oligonucleotides for the treatment of viral infection and allergy.